Software Testing in E-Commerce: A Comparison Between Manual and Automated Testing Using Katalon Studio and Python - Rakly, Brian Duen; Andriyani, Widyastuti (Journal of Artificial Intelligence and Software Engineering, 2025)
Software testing is a crucial element in software development to ensure quality and reliability. This study compares manual and automated testing using tools like Katalon Studio and Python. Manual testing is effective for scenarios requiring human judgment, such as user experience (UX) evaluation. In contrast, automated testing is more efficient for routine and repetitive tasks, reducing human error and speeding up the process. This study evaluates the effectiveness, efficiency, and costs of both methods in the context of e-commerce software testing. The results indicate that manual testing is superior in detecting defects before release, while automated testing is more cost-effective and time-efficient for repetitive testing. This guide assists developer for selecting the appropriate testing method based on their project needs.